2020
DOI: 10.3762/bjoc.16.103
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis with organic dyes: facile access to reactive intermediates for synthesis

Abstract: Organic dyes have emerged as a reliable class of photoredox catalysts. Their great structural variety combined with the easy fine-tuning of their electronic properties has unlocked new possibilities for the generation of reactive intermediates. In this review, we provide an overview of the available approaches to access reactive intermediates that employ organophotocatalysis. Our contribution is not a comprehensive description of the work in the area but rather focuses on key concepts, accompanied by a few sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 190 publications
(257 reference statements)
1
71
0
Order By: Relevance
“…This matches almost perfectly with the absorption maximum of Methylene Blue (MB), a commonly-used photocatalyst (see Fig. 3) [56].…”
Section: The Genesis Of the Lsc-pm Conceptsupporting
confidence: 78%
“…This matches almost perfectly with the absorption maximum of Methylene Blue (MB), a commonly-used photocatalyst (see Fig. 3) [56].…”
Section: The Genesis Of the Lsc-pm Conceptsupporting
confidence: 78%
“…In 2016, it was found that Eosin Y could also operate in aerobic conditions; Su and co-workers demonstrated that thiols could be easily oxidized to disulfides under fluidic conditions by a convenient numbering-up strategy combining up to eight parallel reactors [30]. Even if this work was focused on the evaluation of the feasibility of the numbering-up approach rather than the chemical application, it was possible to synthetize diphenyl sulfide (12) with a high yield operating with 1 mol% of Eosin Y as a photocatalyst in the presence of tetramethylethylenediamine (TMEDA) and pure oxygen (as oxidant) using a multicapillary photomicroreactor system (Scheme 8).…”
Section: Continuous Flow Photocatalytic Oxidation Mediated By Eosin Ymentioning
confidence: 99%
“…Furthermore, organic dyes generally possess no toxic properties and are environmentally benign. Considering the numerous reviews published in the last few years in this very wide field [10][11][12], in the present contribution, only the most recent and significant applications of Eosin Y as an organo-photocatalyst in homogeneous reactions performed under fluidic conditions and in solid-supported catalyst reactions will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…which the quinone iminium salts D5 is formed [29]. The C-centred cation o-CH2TNH2 + is highly reactive [30] and can be transformed either by reaction with certain nucleophiles into the adducts X2 or by reaction with further o-toluidine or aniline (ANH2), via the dimer D6, into the acridines D7 [31] or the Chrysaniline D8 [32].…”
Section: Oxidation States and Reactivity Of Toluidinementioning
confidence: 99%